Cooperation, competition and individualism from a sociocultural constructivist perspective / Cooperação, competição e individualismo em uma perspectiva sócio-cultural construtivista - Marilícia Witzler Antunes Palmieri; Angela Uchoa Branco (Psicologia: Reflexão e Crítica, 2004)
In the present article we argue for the need to develop a conceptual and theorical approach to the study of social motivation, particularly focusing upon the issue of cooperation, competition and individualism. The perspective herein adopted takes into account sociocultural, affective and cognitive dimensions of human social interdependence. We discuss the multiple and diverse components of human motivational system from a systemic and holist viewpoint that emphasizes the contextual and interactive dimensions of developmental processes of value co-constructions, as well as specific patterns of social interactions. The article highlights the need to investigate the topic from a sociocultural constructivist perspective, addressing the methodological issues and, especially, stressing the urge of scientific psychology to contribute to contemporary society by providing a better understanding of processes implied in the development of cooperative, competitive and individualist values.